(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
ObjectiveThis study examines suicide patterns in the Northeastern states of India, often referred to as the Seven Sisters. The aim is to assess whether demographic factors such as gender, marital status, and income group can explain suicide trends, and to explore broader systemic influences. The findings are intended to support forensic medicine professionals, policymakers, and public health authorities in their work.MethodPanel data from the National Crime Records Bureau (2014–2022) were analyzed using a Linear Mixed Model (LMM). This method evaluates both the direct role of demographic variables and the hidden, state-specific influences that may affect suicide rates, such as culture, economy, policies, and social conditions.FindingsThe analysis reveals that demographic factors alone (male/female, married/unmarried, rich/ poor) are not strong predictors of suicide rates. Instead, large-scale, state-level conditions play a more decisive role. Each state shows unique patterns shaped by its own social and systemic environment.ConclusionThese findings emphasize the importance of considering state-specific factors in forensic investigations of suicide. Forensic pathologists and medico legal experts may benefit from this perspective when conducting psychological autopsies, interpreting case patterns, and providing expert opinions. The study also underlines the need for region-specific suicide prevention strategies that can inform both forensic practice and public health policy.